Microfibre ring resonators and principles of fibre optical gyroscope - Jiang, Ping (2013)
This paper researched the theory of Sagnac effect, and four kinds of fibre ring resonators, including a single ring resonator, an Add-drop filter, ring resonator with a Sagnac loop reflector and a twin rings resonator, only 2D structure were considered. Ring resonator with a Sagnac loop reflector was compared with a twin rings resonator based on their performance on transmission characteristics, group delay and fabrication difficulty, and got the conclusion: the Ring resonator with a Sagnac loop reflector which resonance extinction ratio is remarkably enhanced compared with micro-fibre ring resonator without Sagnac interferometer can be used by a twin rings resonator instead.